The Association of Physical Activity with the Severity of Carotid Disease - Vukasinovic, Danka; Maksimovic, Milos; Tanaskovic, Slobodan; Cirkovic, Andja; Vlajinac, Hristina (Medical Research, 2026)
Introduction: Regular physical activity reduces the risk of cardiovascular diseases (CVD). The aim of this study was to examine the association of physical activity with the severity of carotid disease. Materials and methods: This cross-sectional study involved 506 patients from the Vascular Surgery Clinic at the Institute for Cardiovascular Diseases „Dedinje“, who underwent carotid endarterectomy from 2012 - 2017. The severity of carotid disease was assessed based on the degree of carotid stenosis, the type of plaque, and the patients’ symptomatic status before surgery. Patient physical activity data were collected using the standardized Baecke questionnaire. Univariate and multivariate logistic regressions were performed to examine the association between physical activity and the severity of carotid disease. Results: According to the univariate analysis, there was no significant association of any form of physical activity (occupational, sports or recreational) with the degree of carotid stenosis, nor with other characteristics. Also, physical activity was not associated with complicated carotid plaque. The only characteristic associated with complicated carotid plaque was the use of OACs in therapy (OR=2.91; 95% CI=1.12-7.52; p=0.028). The relationship between physical activity and symptomatic carotid disease was not observed, but according to multivariate analysis, the following factors were associated with symptomatic status: age (OR=0.97; 95% CI 0.94-0.99; p=0.016), gender (OR=0.64; 95% CI 0.44-0.99; p=0.028), family history of CVD (OR=0.63; 95%CI 0.43-0.94; p=0.022), use of clopidogrel (OR 1.79; 95% CI 1.18-2.71; p=0.006) and ACEIs in therapy (OR=1.60; 95% CI 1.02-2.53; p=0.041). Conclusion: Physical activity was not associated with the severity of carotid disease.